The Effect of Text Messaging on EFL Learners' Lexical Depth and Breadth - Behnam Behforouz (National Research University Higher School of Economics, 2021)
Using technology in the classroom context can be an effective way to learn a foreign or second language. Vocabulary is considered one of the important skills for identifying a learner's performance in various academic and non-academic contexts. The present paper investigated the effect of text messaging on learners' lexical knowledge and vocabulary size by using mobile learning ( m-learning). After the administration of an Oxford Placement Test, a total of 37 EFL learners were selected as the sample of the study. Before the treatment process, a word association test (WAT) and the updated vocabulary level test (UVLT) were administered as pre-tests. The learners received six vocabulary items selected from their coursebook through SMSs three times a week in addition to the in-class instruction. After finishing the treatment process, the WAT and the UVLT tests were administered again as post-tests to assess the learners' achievement and the effectiveness of the treatment. Since the normality of data distribution was not confirmed, the Wilcoxon signed-rank test was run for mean comparisons. The findings showed no meaningful difference between the pre-tests and post-tests regarding the vocabulary depth scores, while there was a statistically significant difference based on vocabulary breadth. Therefore, it can be claimed that text messaging via m-learning had a significant impact on learners' vocabulary breadth. Curriculum developers and EFL teachers can benefit from the findings of the current study by considering the significance of text messaging for teaching different aspects of lexical knowledge.